2022
DOI: 10.21608/mjcu.2022.264494
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Soft Markers in Obstetric Ultrasound

Abstract: Background: The use of ultrasound in pregnancy has significant health and economic outcomes for families and the health care system. With high resolution ultrasound, it is possible to examine fetal anatomy in great detail. The quality of images obtained today is such that minor deviations from normal can be clearly identified. Aim of Study:The purpose of this prospective study is the observation after detection of ultrasound soft markers, and to evaluate the usefulness of each ultrasound soft marker, and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, more diagnostic tests may be needed to find out the cause of the hyperechogenic bowel. Also, fetal soft markers, such as hyperechogenic bowel, are ultrasound findings that have unclear clinical meaning 14 . Therefore, these findings may have limited clinical impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more diagnostic tests may be needed to find out the cause of the hyperechogenic bowel. Also, fetal soft markers, such as hyperechogenic bowel, are ultrasound findings that have unclear clinical meaning 14 . Therefore, these findings may have limited clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Also, fetal soft markers, such as hyperechogenic bowel, are ultrasound findings that have unclear clinical meaning. 14 Therefore, these findings may have limited clinical impact. A systematic review identified chromosomal abnormalities in 3.3% of fetuses with isolated echogenic bowel.…”
Section: Discussionmentioning
confidence: 99%